2020
DOI: 10.1186/s13102-020-00223-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preoperative low-intensity training with slow movement on early quadriceps weakness after total knee arthroplasty in patients with knee osteoarthritis: a retrospective propensity score-matched study

Abstract: Background Severe and early quadriceps weakness (QW) after total knee arthroplasty (TKA), which is caused by acute inflammation resulting from surgical trauma and tourniquet-induced ischemia-reperfusion (IR) injury, can be especially problematic. We focused on tourniquet-induced IR injury, because it has been shown to be preventable through ischemic and exercise preconditioning. Low-intensity resistance exercise with slow movement and tonic force generation (LST) share some similarities with is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…One of the leading causes of extension lag may be quadriceps femoris dysfunction due to abnormal reflexes [ 28 ]. In addition, pain from surgery, damage to soft tissues, and swelling inhibit normal knee joint movements [ 4 , 29 ]. The BES generated when the patient attempted to extend the knee joint was detected by the HAL-SJ, which synchronized the extension with the intended motion.…”
Section: Discussionmentioning
confidence: 99%
“…One of the leading causes of extension lag may be quadriceps femoris dysfunction due to abnormal reflexes [ 28 ]. In addition, pain from surgery, damage to soft tissues, and swelling inhibit normal knee joint movements [ 4 , 29 ]. The BES generated when the patient attempted to extend the knee joint was detected by the HAL-SJ, which synchronized the extension with the intended motion.…”
Section: Discussionmentioning
confidence: 99%
“…However, no significant differences in increased oxidative stress, knee and thigh swelling, and knee pain during the QST performed immediately after TKA were observed between the groups. Several studies on human models have shown that QW can be caused by knee swelling, knee pain, and quadriceps muscle atrophy 3,5,6) , which are partially induced by tourniquet application during TKA 7,8) . Tourniquet application and its subsequent release can induce IR injuries 28) .…”
Section: Discussionmentioning
confidence: 99%
“…Pre-and postoperative evaluations, which were performed at 1 month before surgery and again on postoperative day 4, included measurements of serum d-ROM levels, knee circumference at 1 and 10 cm proximal to the upper edge of the patella, knee pain during the QST, and quadriceps strength. The thigh volume was calculated via the truncated cone method, as previously described 6) . This method has shown to be excellent criterion-related validity, intra-rater reliability, and good inter-rater reliability 20) .…”
Section: Participants and Methodsmentioning
confidence: 99%
See 2 more Smart Citations